2011
DOI: 10.5395/jkacd.2011.36.6.483
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycerin on the surface hardness of composites after curing

Abstract: Objectives:The purpose of this study was to examine the effect of glycerin topical application on the surface hardness of composite after curing. Materials and Methods: A composite (Z-250, 3M ESPE) was packed into a disc-shaped brass mold and light cured according to one of the following protocols. Group 1 (control) was exposed to air and light cured for 40 sec, group 2 was covered with a Mylar strip and light cured for 40 sec, group 3 was surface coated with glycerin and light cured for 40 sec, and group 4 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 17 publications
2
15
0
9
Order By: Relevance
“…Em sentido oposto, os valores de microdureza mais baixos obtidos com as matrizes de PVS poderão ser indicativos de inibição da polimerização do compósito por interação química com os componentes dos PVS utilizados 8 39 , que impediria uma correta avaliação da microdureza. No entanto, nenhum dos procedimentos permitiu atingir valores de microdureza semelhantes aos observados nos espécimes polimerizados através de matriz de acetado, o que poderá indicar uma remoção eficaz da camada inibida com estes procedimentos, resultados que estão de acordo com a literatura 13 . Assim foi rejeitada a terceira hipótese nula em estudo.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Em sentido oposto, os valores de microdureza mais baixos obtidos com as matrizes de PVS poderão ser indicativos de inibição da polimerização do compósito por interação química com os componentes dos PVS utilizados 8 39 , que impediria uma correta avaliação da microdureza. No entanto, nenhum dos procedimentos permitiu atingir valores de microdureza semelhantes aos observados nos espécimes polimerizados através de matriz de acetado, o que poderá indicar uma remoção eficaz da camada inibida com estes procedimentos, resultados que estão de acordo com a literatura 13 . Assim foi rejeitada a terceira hipótese nula em estudo.…”
Section: Resultsunclassified
“…Desta forma propõe-se no futuro desenvolver estudos que permitam resolver este problema, nomeadamente com utilização de produtos como a glicerina, que possam impedir a inibição da polimerização quando se utilizam estes materiais 13,38 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Consequently, the lowest hardness value was registered by the group with an immersion time of 120 minutes, but without the application of glycerin. 9,14 It can be concluded that the application of glycerin is capable of increasing the hardness of composite resins immersed in tamarind soft drinks.…”
Section: R • + O2 = R-oo • Free Radicals + Oxygen = Peroxyl Radicalsmentioning
confidence: 99%
“…Hence, glycerin can be used as a barrier to prevent the formation of OIL on occlusal surfaces or those of composite resins that are difficult to access. 9 Another factor affecting the hardness of composite resins is the absorption of water present in the food and beverage consumed daily by patients and in direct contact with tooth surfaces. 10 Soft drinks constitute one popular beverage consumed by the Indonesian public with annual per capita consumption within the country amounting to 33 liters.…”
Section: Introductionmentioning
confidence: 99%